A ribosomally synthesized and posttranslationally modified peptide with ADP-ribosylation - Sijia Guo; Suze Ma; Lulu Song; Jun Wang; Tonghai Liu; Wupeng Yan; Wei Zhang; Zixin Deng; Wei Ding; Qi Zhang (Proceedings of the National Academy of Sciences, 2026)
Ribosomally synthesized and posttranslationally modified peptides (RiPPs) are a fertile ground for uncovering new enzymatic chemistry and structural complexity. Here, we describe minviopeptin, an unusual ADP-ribosylated triceptide accessed through heterologous expression of a cryptic biosynthetic gene cluster. Structural and functional analyses reveal a combination of crosslinking, ADP-ribosylation, and oxidative peptide cleavage, underscoring the capacity of RiPP pathways to generate densely functionalized molecular scaffolds. By revealing ADP-ribosylation as a previously unrecognized RiPP modification and exposing reactivity within radical SAM and nonheme iron enzymes, this work broadens the landscape of RiPP biosynthetic chemistries and offers opportunities for natural product diversification and peptide engineering.